The Structure of Proboscis Monkey (Nasalis larvatus) Population in the Area of BatuSawar Mountain Hulu Sungai Tengah District - Fauzan, Nahri; Akhmad Naparin, Kaspul (Proceeding Biology Education Conference: Biology, Science, Enviromental, and Learning, 2015)
Proboscis monkey (Nasalislarvatus) is a species of primates endemic in Borneo. According to South Borneo Governor's Decree No. 29 Year 1990 dated January 16 at1990, proboscis monkey is set to be a mascot fauna of South Borneo Province. The habitat of proboscis monkeys are usually found along the rivers and swamp areas in Borneo. Research of proboscis monkeys who live in mountainous areas are still very rarely done so little known by the public. Therefore , to determine the condition of proboscis monkeys in a habitat of them to do research on the structure of the population. The purpose of this study was to calculate the number , density and age structure of the population pyramid illustrates the proboscis monkey (Nasalislarvatus). The method used is descriptive method by calculating the concentration technique (concentration count). The study was conducted on a population proboscis monkey (Nasalislarvatus)Â  in the area of BatuSawar Mount in Hulu Sungai Tengah District. Data analysis was performed by direct calculation during primate visible. The largest number of individuals encountered on a whole series of observations is assumed as the number of individuals that represent a group, whereas the smallest number of individuals encountered is assumed that the other individual is not visible at the time of observation.The observation of the proboscis monkeys (Nasalislarvatus) found in the area of research were adult proboscis monkey amounted to 17 with a density of 0,028 ind / ha, totaling 23 juveniles proboscis monkey with a density of 0.038 ind / ha, and child proboscis monkey amounted to 13 with a density of 0,022 ind / ha. The population structure of proboscis monkey (Nasalislarvatus) in the area of BatuSawarmountain in Hulu Sungai Tengah district if depicted using the age pyramid, the pyramid form a jug or bowl.Keywords: Proboscis Monkey, population structure, Batu Sawar Mountain